Back Calculation from Geotechnical Structures Response around Kuala Lumpur - Lee , Ee Keng (Universiti Teknologi Petronas, 2009)
It is well recognized that uncertainties are abundant in geotechnical engineering which may result in failure of geotechnical structures. Achieving an idealized parameters' literature has become a form of approach analysis but the accurate determination of soil parameters is rather difficult. The main focus of this study is to evaluate aspects of computational geotechnics through inverse analysis to deduce design parameters through correlation with field monitoring data of various high rise residential developments around Kuala Lumpur, mainly focusing on soil-structure interaction during Simulation of Basement Excavation and Construction